Peter Explains Spirit Baptism (Acts 11:13-18) - Matthew Glass (Jurnal Penggerak, 2023)
Spirit baptism is a commonly misunderstood doctrine. Typically, systematic theology provides an explanation of a doctrine by examining all the relevant texts on a topic and offering logical conclusions based upon those texts. However, systematic theology must be built upon sound biblical exegesis using a proper exegetical method. The modest aim of this article, then, is to use a proper exegetical method and provide sound biblical exegesis on one text that must be given its due weight in the debate about Spirit baptism.